Determinants of Knowledge and Attitude related to Palliative Care Nurses - Fauziningtyas, Rista; Widowati, Dwi Eri Retno; Indarwati, Retno; Asmoro, Candra Panji (International Journal of Psychosocial Rehabilitation, 2020)
There are only a few health care institutions in Indonesia that carry out palliative care. The factors that are related to the knowledge and attitudes of the health workers who work in the palliative care services are still unknown. The aim of this study was to find out the determinants of the factors related to the nurses' knowledge and attitude in the context of palliative care in a hospital in Surabaya. This study used a cross-sectional design. The sample size was 115 respondents via total sampling. The independent variables were age, education, training experience, length of work and place on the career ladder. The dependent variables were knowledge and the attitude of the nurses toward palliative care. The data was obtained through a questionnaire and it was analyzed using Chi- square, Spearman rho and a multiple linear regression test. There was found to be a relationship between age (p = 0.004) and length of work (p = 0.016) with knowledge in palliative care. There was also found to be a relationship between the length of work (p = 0.049) and career ladder (p = 0.013) with the nurse’s attitude in palliative care. It is expected that the nurses in the hospital can take part in training so then their knowledge will increase. In addition, the arrangement of the career ladder also needs to be clear to create positive behaviors among the palliative nurses. The quality of the palliative services will increase as a result.